2008
DOI: 10.1177/0146167208318601
|View full text |Cite
|
Sign up to set email alerts
|

Mirror, Mirror on the Wall: Enhancement in Self-Recognition

Abstract: People's inferences about their own traits and abilities are often enhancing. A series of experiments suggests that this enhancement extends to more automatic and perceptual judgments as well, such that people recognize their own faces as being more physically attractive than they actually are. In each experiment, participants' faces were made more or less attractive using a morphing procedure. Participants were more likely to recognize an attractively enhanced version of their own face out of a lineup as thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
139
2
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(156 citation statements)
references
References 46 publications
4
139
2
1
Order By: Relevance
“…Whereas Sigmund Freud (1915Freud ( /1961aFreud ( , 1923Freud ( /1961bFreud ( , 1926Freud ( /1961c and Anna Freud (1936/1946 believed that the ego defenses were invoked to repress sexual and aggressive urges, the social-psychological use of self-protection and self-enhancement motives applies to any self-related interest, including perceptions of own faces, abilities, social and physical traits, moral standing, beliefs, and values (Dunning, 1999;Epley & Whitchurch, 2008;. Social and personality psychologists have, therefore, expanded considerably the scope of interests to which the self-enhancement and self-protection motives apply.…”
Section: Implicit Versus Explicit Aspectmentioning
confidence: 99%
“…Whereas Sigmund Freud (1915Freud ( /1961aFreud ( , 1923Freud ( /1961bFreud ( , 1926Freud ( /1961c and Anna Freud (1936/1946 believed that the ego defenses were invoked to repress sexual and aggressive urges, the social-psychological use of self-protection and self-enhancement motives applies to any self-related interest, including perceptions of own faces, abilities, social and physical traits, moral standing, beliefs, and values (Dunning, 1999;Epley & Whitchurch, 2008;. Social and personality psychologists have, therefore, expanded considerably the scope of interests to which the self-enhancement and self-protection motives apply.…”
Section: Implicit Versus Explicit Aspectmentioning
confidence: 99%
“…Decreasing homogeneity in facial skin coloration in both sexes leads to the perception of being older, less healthy, and less attractive (10). An important reason for the use of cosmetics in women is to appear to have spotless, flawless skin and an overall young and healthy appearance (90).…”
Section: Facial Beauty: Smooth Skinmentioning
confidence: 99%
“…It has been reported that when people are evaluating their own level of attractiveness, they have a self-serving bias, and often find themselves more attractive than they are evaluated by others (10,11). Studies indicate that people find themselves, on average, 10% more attractive than they actually are (10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Patterns such as this can be seen in the planning fallacy, where people tend to be overconfident in the time it will take them to complete tasks, but their estimates nonetheless remain highly correlated with their completion times (Buehler, Griffin, & Ross, 1994). Further, when individuals are asked to identify pictures of themselves from an array of photos morphed to be more or less attractive, on average they choose a photo that is morphed 20% more attractive, rather than photos morphed to a greater degree (Epley & Whitchurch, 2008). Thus, the self-limiting nature of overconfidence should ensure that confidence remains a signal with a substantial amount of 'truth value', reconciling the social hypothesis of overconfidence with signalling theory.…”
Section: Honest Signalsmentioning
confidence: 99%